Pitahaya aging diagnostic by impedance/capacitance spectroscopy - Cortes, Henry; Edgar, Villegas; Suarez, Rócio; Castillo, Jos; Gonçalves, Lus Moreira; Bueno, Paulo R. [UNESP] (Springer, 2015)
Impedimetric/capacitive analyses were used as a non-destructive analytical tool for the determination of yellow pitahaya (Selenicereus megalanthus Haw.) aging. Pitahaya is an exotic fruit of increasing commercial importance, in which sensing the level of maturation plays a major role. The impedimetric analysis of the fruit's normal deterioration was performed with a homemade probe with two needle silver electrodes. The most sensitive changes on the impedance/capacitance spectra were found at a low-frequency region, where it was possible to build a linear analytical curve between the instrumental response and the aging time.
Keywords: Bioimpedimetry; Biosensor; Fruit analysis; Food quality